2020
DOI: 10.1111/psyp.13519
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insula activity and the effect of agency on the Stimulus‐Preceding Negativity

Abstract: If you know that you are the author of a freely chosen action and that you bear responsibility for its outcome, then you are said to have “a sense of agency.” When there is a delay between action and outcome, this response must be remembered if you are to learn from the experience. Previous studies have shown that the Stimulus‐Preceding Negativity (SPN) recorded during the delay interval is larger under conditions that foster a sense of agency. In an EEG experiment (N = 27), we confirmed that the SPN is larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 62 publications
5
20
0
Order By: Relevance
“…At the neural level, we observed that adolescents with higher levels of social anxiety displayed heightened SPN activity during social feedback anticipation. This effect was found at the right frontal cluster, which corresponds with prior studies demonstrating frontal dominance of the SPN ( Hackley et al, 2020 ; Kotani et al, 2015 , 2009 ; Masaki et al, 2010 ). We observed that the right frontal SPN was more negative for the anticipation of acceptance versus rejection feedback among adolescents with higher social anxiety symptoms, but this effect was not significant.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…At the neural level, we observed that adolescents with higher levels of social anxiety displayed heightened SPN activity during social feedback anticipation. This effect was found at the right frontal cluster, which corresponds with prior studies demonstrating frontal dominance of the SPN ( Hackley et al, 2020 ; Kotani et al, 2015 , 2009 ; Masaki et al, 2010 ). We observed that the right frontal SPN was more negative for the anticipation of acceptance versus rejection feedback among adolescents with higher social anxiety symptoms, but this effect was not significant.…”
Section: Discussionsupporting
confidence: 88%
“…Our sample did not include adults precluding us from directly comparing adults and adolescents and identifying possible developmental differences in the lateralization of the SPN. Although, there are mixed findings regarding localization of the SPN in other tasks, several studies suggest a right preponderance of the SPN which is thought to arise from the right insular reactivity ( Brunia et al, 2011 ; Hackley et al, 2020 ; Kotani et al, 2015 , 2009 ). The effects we found prominently for the right clusters might be, therefore, explained by the lateral localization of the SPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know from source localization research (Böcker et al, 1994; Catena et al., 2012), including fMRI‐EEG studies (Hackley et al., 2020; Kotani et al., 2015; Seidel et al., 2015; Tsukamoto et al., 2006), that multiple cortical regions contribute to the SPN. To determine if activity within any of these sources reflects hypothetical constructs related to learning (e.g., holding an outcome prediction in mind), it will be necessary to fractionate the SPN into subcomponents.…”
Section: Discussionmentioning
confidence: 99%
“…When the outcome of an action is delayed by a few seconds, scalp recordings show a frontally distributed negativity, the stimulus‐preceding negativity (SPN), whose amplitude increases with task difficulty (Mattox et al., 2006), with the amount of feedback information (Kotani et al., 2003), and with knowledge regarding feedback veracity (Chwilla & Brunia, 1991). Pertinent to the credit assignment problem is the fact that SPN amplitude is considerably enhanced when the participant has perceived control over the action outcome; in other words, that he or she has a sense of agency (Hackley et al., 2020; Masaki et al., 2010; Mei et al., 2018; Muhlberger et al, 2017). A finding of direct relevance to the current study is that SPN amplitude has been reported to decrease over the course of learning in three very different tasks: perceptual categorization (Morís et al., 2013), cognitive extrapolation (Hirao et al., 2017), and fine motor control (Ren et al., 2017).…”
Section: Introductionmentioning
confidence: 99%